Peningkatan kreativitas menulis cerpen dengan media koran pada siswa kelas IX - Widarminto Widarminto (Persatuan Guru Republik Indonesia Kota Banjarbaru, 2022)
This study seeks to improve students' ability to determine the story line and then assemble it into sentences which can eventually form an interesting short story. This type of research is Classroom Action Research (CAR) with quantitative descriptive. The research location is in SMP Negeri 4 Bontang. Subjects who were subjected to action in this study were students of class IX A SMP Negeri 4 Bontang, totaling 34 students. The results of the study stated that learning to write short stories using newspaper news media could improve achievement and interest in learning for class IX A students of SMP Negeri 4 Bontang.